DAMPAK PENGEMBANGAN PROGRAM EKOWISATA BERBASIS SATWA ENDEMIK DI TANGKOKO BITUNG - Baware, Fergina; Kiroh, H.J.; Wungow, R.H.; Kawatu, M. (Universitas Sam Ratulangi, 2017)
THE IMPACT OF ENDEMIC ECOTOURISM PROGRAM DEVELOPMENT BASED ONÂ TANGKOKO Â NATURE RESERVE OF BITUNG. Tangkoko National Reserve is one of the nature reserves located in Bitung regency of North Sulawesi. The reserve covers an area of 8,745 hectares. There is abundant biodiversity such as various types of protected flora and fauna can be found in the reserve. Among them there are endemic wildlifes such as Sulawesi Macaque (Macaca nigra), Tarsiers (Tarsius spectrum), the Sulawesi bear cuscus (Ailurops ursinus), and Hornbill (Rhyticeros cassidix). Here is where the tourists can enjoy the beauty of the reserve or seen firsthand the wealthy of nature in such a protected forest, where the forest has potential as anecotourism spot. Tourism industry has an important role in the development efforts and the development of the region where the tourism spot located.Even in some areas show that tourism industry is able to develop the region as well as create a main income source. The present study was conducted to elaborate the impacts of endemic ecotourism program development basedon the development of Tangkoko nature reserve of Bitung. The study was conducted from November 2016 to January 2017. The ellaboration of the study was focused on the impact of ecotourism developmentonthe existing endemic Sulawesi Black Monkeys and Tarsiers. Survey method was employed to collect and analyze various data and information on endemic fauna of Sulawesi Black Monkeys and Tarsiers. The primary data was obtained through direct interviews with various communities around nature reserve area, and secondary data was obtained from related government sources in Bitung regency.Variables observed were:1) vegetation, 2) the existing wildlife conditions, 3) community income, and 4) the income of the region of Bitung regency.Based on results and discussion, it can be concluded that ecotourism is the best program to be implemented as it could give positive impact towards conservation efforts,increase community's income, and regional income.Keywords: Tangkoko reserve, Ecotourism, Endemic Fauna.